Spiritism in the Novel Paola: novelina espiritista, by Jaime Gálvez - Murillo Ramírez, Guillermo (2023)
To study the novel Paola: novelina espiritista (1922), by Jaime Gálvez, the principles of Allan Kardec are applied along with religious symbolisms and characters (medium and ghost). From the perspective of a literary-criticism approach, a description is provided of spiritism as an esoteric science, the sociohistorical development of the phenomenon under study, both in Costa Rica and in Latin America, and its appearance as a theme in various samples of Costa Rican literature.